Preparation method of composite formaldehyde removal agent and product and application thereof

By introducing active amino groups and polyetheramines on the surface of nanotitanium dioxide, combining chemical reactions and photocatalytic effects, the problem of rapid and efficient but not continuous but not rapid in the prior art is solved, and the rapid and efficient and continuous formaldehyde removal effect is achieved. .

CN119425653APending Publication Date: 2025-02-14SHANGHAI NAT ENG RES CENT FORNANOTECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411573619.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing formaldehyde removal technology has the problems of rapid, efficient but not continuous, continuous but not rapid, high cost or prone to agglomeration and inactivation, and it is difficult to meet the aldehyde removal needs at different time stages.

Method used

The reaction between alcohol hydroxyl groups on the surface of nanotitanium dioxide and polyetheramines is prepared by polyol solvent thermal reaction, and the reaction of active amino groups is introduced, combining chemical reactions and photocatalytic effects to achieve rapid, efficient and continuous formaldehyde removal effects.

Benefits of technology

It achieves rapid and efficient removal of formaldehyde in the initial stage, and continuously degraded formaldehyde through photocatalysis in the subsequent stage, meeting the aldehyde removal needs at different time stages, and avoiding the problem of agglomeration and inactivation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425653A_ABST
    Figure CN119425653A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a composite formaldehyde removal agent as well as a product and application of the composite formaldehyde removal agent, an alcoholic hydroxyl group on the surface of nano titanium dioxide prepared through a polyol solvothermal reaction reacts with polyether amine, active amino groups are introduced to the surface of nano titanium dioxide, and the obtained composite formaldehyde removal agent is used for rapidly and durably removing formaldehyde. When the nano titanium dioxide is used as a formaldehyde removal agent, the formaldehyde is quickly and efficiently removed by utilizing a chemical reaction between active amino groups combined on the surface of the nano titanium dioxide and the formaldehyde in an initial stage until active amino groups are completely consumed. And in the subsequent stage, the formaldehyde is continuously degraded by the photocatalytic effect of the nano titanium dioxide, so that the requirements on formaldehyde removal in different time stages in an actual life scene are met. In addition, polyether amine molecules combined on the surface of the nano titanium dioxide serve as a surfactant to achieve a good dispersion effect, agglomeration of the nano titanium dioxide is inhibited, and the photocatalytic effect of the nano titanium dioxide is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of daily chemical industry, and specifically relates to a preparation method of a composite formaldehyde remover, a product thereof and an application thereof. Background Art

[0002] Materials such as plywood, laminate flooring, doors, wardrobes, and cabinets used in home decoration will emit formaldehyde. Due to the special irritating smell of formaldehyde, the human body will experience various discomfort symptoms when exposed to a certain concentration of formaldehyde gas. The national standard GB50325-2020 "Code for Indoor Environmental Pollution Control of Civil Construction Engineering" stipulates that the concentration of formaldehyde in the indoor environment must be less than 0.08 mg / m 3 . Commonly used methods for removing formaldehyde from indoor environments include plant absorption, physical adsorption, chemical reaction, thermal catalytic oxidation, photocatalytic degradation, plasma, etc. At present, various methods for removing formaldehyde have advantages and disadvantages, so they are all used in actual formaldehyde removal scenarios. Plants are green and environmentally friendly, but the absorption effect is slow. The physical adsorption method is easy to operate, but there are problems of adsorption saturation and secondary pollution. The chemical reaction method uses the direct chemical reaction of active amino groups with formaldehyde, and the immediate formaldehyde removal effect is significant, but there is also the problem of reaction saturation. At the same time, during the storage process, the active amino group will react with acidic gases such as carbon dioxide in the environment and be gradually consumed, thereby losing the formaldehyde removal performance. The thermal catalytic oxidation method is energy-saving and environmentally friendly, and has high degradation efficiency, but it requires the use of precious metals such as Pt, Au, Pd, and Ir as catalysts, which is expensive. The photocatalytic degradation method can completely degrade formaldehyde into carbon dioxide and water, but the nano-metal oxides used as photocatalysts are prone to agglomeration and inactivation, resulting in a decrease in degradation efficiency. It can be seen that the development of a composite mechanism formaldehyde removal product will have a high market prospect. The patent with application number 202110937895.1 discloses a formaldehyde remover, which adopts a composite formula and contains a variety of effective formaldehyde removal ingredients, such as biodegradable enzymes, organic matter A and photocatalysts. Among them, organic matter A is an organic acid or an organic base. The composite formula of the formaldehyde remover is merely a physical mixture of formaldehyde removal substances with different formaldehyde removal mechanisms, and fails to exert its synergistic function.

[0003] In addition, the requirements for formaldehyde removal performance in real scenarios are different. For newly renovated indoor spaces, various wooden furniture or wallpapers emit a large amount of formaldehyde, and fast and efficient formaldehyde removal performance is required to quickly reduce the formaldehyde concentration in a short period of time. After several weeks of decoration, the formaldehyde enclosed in the wood will continue to be released slowly, and at this time, continuous formaldehyde removal performance is required. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the present invention aims to provide a composite formaldehyde scavenger and a preparation method thereof.

[0005] Another object of the present invention is to provide a composite formaldehyde-removing agent product prepared by the above method.

[0006] Another object of the present invention is to provide an application of the above product.

[0007] The object of the present invention is achieved by the following scheme: A method for preparing a composite formaldehyde removal agent, using the reaction of alcohol hydroxyl groups on the surface of nano-titanium dioxide prepared by thermal reaction of polyol solvent with polyether amine to introduce active amino groups on the surface of nano-titanium dioxide, comprising the following steps: (1) Precursor preparation Under stirring conditions, alkoxy titanate is added dropwise to low-carbon diol, wherein the volume ratio of the alkoxy titanate to the low-carbon diol is (2.5-5.0):100, and stirring is continued at 30-40°C for 1-2 h. After the mixture is evenly mixed and no white precipitate appears, polyetheramine is added, wherein the molar ratio of the polyetheramine to the alkoxy titanate is 0.2-0.5:1.0, and stirring is continued for 1-2 h to obtain a transparent light yellow solution; (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) is transferred to a polytetrafluoroethylene-lined stainless steel high-pressure reactor with a filling degree of 65-80%, and the reactor is placed in an oven and reacted at 140-180° C. for 14-18 h. After the reaction is completed, the reaction is cooled to room temperature to obtain a reaction product; (3) Treatment of reaction products The reaction product obtained in step (2) was washed three times with water and ethanol respectively, and centrifuged at 10000 rpm to obtain modified nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 60-80 °C for 10-12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

[0008] Wherein, the chemical structural formula of the polyetheramine is: In the polyetheramine structural formula, m is 2-8 and n is 2-8.

[0009] The alkoxy titanate is one of n-butyl titanate and tetraisopropyl titanate.

[0010] The low-carbon diol is one of ethylene glycol, 1,3-propylene glycol and 1,4-butanediol.

[0011] The present invention also provides a composite formaldehyde remover, which is prepared according to any of the above methods.

[0012] The present invention also provides an application of a composite formaldehyde removal agent in removing formaldehyde, which has a rapid and lasting formaldehyde removal effect.

[0013] Formaldehyde removal performance test 1.0 g of the product of the present invention and the formaldehyde remover prepared in Comparative Examples 1 to 3 were respectively weighed, dispersed in 100.0 mL of deionized water, and dispersed by ultrasonic wave with a power of 250 W for 10 min to obtain a formaldehyde remover dispersion.

[0014] 1 m 2 The commercially available particle board was placed in a 1.5 m 3 The test chamber was filled with 100 mL of formaldehyde-removing agent dispersion prepared above (the temperature in the test chamber was maintained at 25 ± 0.5 °C and the relative humidity was maintained at 50 ± 2%). The fan in the test chamber was turned on and stirred for 1 min to mix the air in the chamber with the formaldehyde released by the particle board, and then the fan was turned off. The formaldehyde concentration in the test chamber was tested as the initial concentration using a nationally certified formaldehyde detector (CMA level). There was no need to turn the fan on and off for subsequent formaldehyde concentration tests. 100.0 mL of the formaldehyde-removing agent dispersion prepared above was sprayed on the particle board three times (the next spray was conducted after the liquid sprayed last time was dried), and the formaldehyde concentration in the test chamber was tested at regular intervals (tested 3 times at 1 day, 3 days, and 7 days in the first 7 days; tested once a week after 7 days; tested once every four weeks after 28 days, until 84 days) to evaluate the formaldehyde removal effect of the formaldehyde-removing agent.

[0015] The formaldehyde removal mechanism of the present invention is: utilizing the reaction of alcoholic hydroxyl groups on the surface of nano-titanium dioxide prepared by thermal reaction of polyol solvents with polyetheramines, when active amino groups are introduced on the surface of nano-titanium dioxide as formaldehyde removers, in the initial stage, the chemical reaction between active amino groups bound to the surface of nano-titanium dioxide and formaldehyde is utilized to quickly and efficiently eliminate formaldehyde until the active amino groups are completely consumed. In the subsequent stage, the photocatalytic effect of nano-titanium dioxide continues to degrade formaldehyde, thereby meeting the demand for formaldehyde removal at different time stages in actual life scenarios. In addition, the polyetheramine molecules bound to the surface of nano-titanium dioxide act as a surfactant to play a good dispersing role, inhibiting the agglomeration of nano-titanium dioxide, thereby ensuring the performance of its photocatalytic effect.

[0016] Compared with the prior art, the composite formaldehyde remover of the present invention has the following advantages: 1. As a composite catalyst, it has both the characteristics of rapid and efficient formaldehyde removal through chemical reaction and the environmentally friendly and continuous formaldehyde removal performance of photocatalyst.

[0017] 2. It can meet the needs of formaldehyde removal at different time stages in real life scenarios. In the initial stage, the chemical reaction between the active amino groups bound to the surface of nano-titanium dioxide and formaldehyde is used to quickly and efficiently eliminate formaldehyde until the active amino groups are completely consumed. In the subsequent stage, the photocatalytic effect of nano-titanium dioxide can continuously degrade formaldehyde.

[0018] 3. The polyetheramine molecules bound to the surface of nano-titanium dioxide act as a surfactant and play a good dispersing role, inhibiting the agglomeration of nano-titanium dioxide and ensuring its photocatalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope (SEM) image of the composite formaldehyde removal agent of Example 1; Figure 2 Curves showing changes in formaldehyde concentration over time in the examples and comparative examples. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described below according to specific embodiments. The protection scope of the present invention is not limited to the following embodiments, which are listed only for illustrative purposes and do not limit the present invention in any way.

[0021] Example 1 A composite formaldehyde remover is prepared according to the following steps: (1) Precursor preparation 3.5 mL of tetraisopropyl titanate was added dropwise to 100.0 mL of 1,3-propylene glycol, and stirred at 30 °C for 2 h. After the mixture was evenly mixed and no white precipitate appeared, 1.97 g of polyetheramine (m=4, n=4) was added, i.e., the molar ratio of polyetheramine (m=4, n=4) to tetraisopropyl titanate was 0.35:1.0, and the mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 69%. The autoclave was placed in an oven and reacted at 140° C. for 18 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reaction product treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 60°C for 12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

[0022] Example 2 The composite formaldehyde remover of this embodiment is prepared according to the following steps: (1) Precursor preparation 3.5 mL of tetraisopropyl titanate was added dropwise to 100.0 mL of 1,3-propylene glycol, and stirred at 30 °C for 2 h. After the mixture was evenly mixed and no white precipitate appeared, 2.20 g of polyetheramine (m=2, n=8) was added, i.e., the molar ratio of polyetheramine (m=2, n=8) to tetraisopropyl titanate was 0.35:1.0, and the mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 69%. The autoclave was placed in an oven and reacted at 140° C. for 18 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reactant treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 60°C for 12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

[0023] Example 3 The composite formaldehyde remover of this embodiment is prepared according to the following steps: (1) Precursor preparation 3.5 mL of tetraisopropyl titanate was added dropwise to 100.0 mL of 1,3-propylene glycol, and stirred at 30 °C for 2 h. After the mixture was evenly mixed and no white precipitate appeared, 2.60 g of polyetheramine (m=8, n=2) was added, i.e., the molar ratio of polyetheramine (m=8, n=2) to tetraisopropyl titanate was 0.35:1.0, and the mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 69%. The autoclave was placed in an oven and reacted at 140° C. for 18 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reactant treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 60°C for 12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

[0024] Example 4 The composite formaldehyde remover of this embodiment is prepared according to the following steps: (1) Precursor preparation 2.5 mL of n-butyl titanate was added dropwise to 100.0 mL of 1,3-butanediol, and stirred at 40°C for 1 h. After the mixture was evenly mixed and no white precipitate appeared, 0.70 g of polyetheramine (m=4, n=4) was added, i.e., the molar ratio of polyetheramine (m=4, n=4) to n-butyl titanate was 0.2:1.0. The mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 68%. The autoclave was placed in an oven and reacted at 180° C. for 14 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reactant treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 80°C for 10 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

[0025] Example 5 The composite formaldehyde remover of this embodiment is prepared according to the following steps: (1) Precursor preparation 5.0 mL of n-butyl titanate was added dropwise to 100.0 mL of ethylene glycol, and stirred at 30°C for 2 h. After the mixture was evenly mixed and no white precipitate appeared, 3.48 g of polyetheramine (m=4, n=4) was added, i.e., the molar ratio of polyetheramine (m=4, n=4) to tetraisopropyl titanate was 0.5:1.0, and the mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 70%. The autoclave was placed in an oven and reacted at 160° C. for 16 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reactant treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 80°C for 10 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

[0026] Comparative Example 1 The reaction steps and raw materials of Comparative Example 1 are the same as those of Example 1, except that the added mass of polyetheramine (m=4, n=4) is 0 g, that is, no polyetheramine (m=4, n=4) is added to obtain nano titanium dioxide powder without polyetheramine modification, which is used as a formaldehyde scavenger for formaldehyde removal performance testing.

[0027] Comparative Example 2 Polyetheramine (m=4, n=4) was directly used as a formaldehyde removal agent to carry out formaldehyde removal performance tests.

[0028] Comparative Example 3 0.94 parts by weight of the titanium dioxide powder prepared in Comparative Example 1 and 1.01 parts by weight of polyetheramine (m=4, n=4) were weighed and stirred to mix the two evenly, simulating the physical mixing state of the titanium dioxide powder and the polyetheramine, and the formaldehyde removal performance test was performed.

[0029] Formaldehyde removal performance test 1.0 g of the formaldehyde scavengers prepared in Example 1 and Comparative Examples 1 to 3 were respectively weighed and dispersed in 100.0 mL of deionized water, and ultrasonically dispersed at a power of 250 W for 10 min to obtain a formaldehyde scavenger dispersion.

[0030] 1 m 2 The commercially available particle board was placed in a 1.5 m 3 The test chamber was filled with a volume of 2500 g (maintaining the temperature in the test chamber at 25±0.5℃ and the relative humidity at 50±2%). The fan in the test chamber was turned on and stirred for 1 min to mix the air in the chamber with the formaldehyde released by the particle board, and then the fan was turned off. The formaldehyde concentration in the test chamber was tested using a nationally certified formaldehyde detector (CMA level) as the initial concentration. There is no need to turn the fan on and off for subsequent tests of formaldehyde concentration. Spray 100.0 mL of the formaldehyde remover dispersion prepared above on the particle board three times (wait for the last sprayed liquid to dry before spraying the next time), and test the formaldehyde concentration in the test chamber at regular intervals (test 3 times at 1 day, 3 days, and 7 days in the first 7 days; test once a week after 7 days; test once every four weeks after 28 days, until 84 days) to evaluate the formaldehyde removal effect of the formaldehyde remover. The data are shown in Table 1. The relevant data are plotted as a line graph. Figure 2 .

[0031] Comparative Example 1 is a nano titanium dioxide powder that has not been modified by polyetheramine. It has a continuous photocatalytic degradation of formaldehyde performance, but it is not as fast and efficient as chemical reaction to remove formaldehyde. As time goes on, the formaldehyde concentration continues to slowly decrease, but it is higher than the formaldehyde concentration of Example 1. Comparative Example 2 is a polyetheramine, which can directly react chemically with formaldehyde to remove formaldehyde. The formaldehyde concentration drops rapidly in the early stage, but as the particle board continues to emit formaldehyde, the polyetheramine loses its ability to remove formaldehyde due to saturation or failure. As time goes on, the formaldehyde concentration slowly increases. Comparative Example 3 is a physical mixture of nano titanium dioxide powder and polyetheramine that has not been modified by polyetheramine. The formaldehyde concentration drops rapidly in the early stage until the reaction is saturated. Nano titanium dioxide powder fails to fully exert its photocatalytic effect due to agglomeration. As time goes on, the formaldehyde concentration decreases slightly. Example 1 is a nano titanium dioxide powder modified by polyetheramine. In the early stage, the polyetheramine combined with the nano titanium dioxide powder quickly removes formaldehyde, and the formaldehyde concentration drops rapidly. Due to the dispersion of polyetheramine molecules, nano-titanium dioxide has no agglomeration phenomenon, the photocatalytic effect is fully exerted, and the formaldehyde is continuously and effectively degraded, and the formaldehyde concentration continues to decrease significantly. Those skilled in the art should note that the embodiments described in the present invention are merely exemplary, and various other substitutions, changes and improvements may be made within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but only to the claims.

Claims

1. A method for preparing a composite formaldehyde remover, characterized in that The active amino groups are introduced on the surface of nano-titanium dioxide by the reaction of alcohol hydroxyl groups on the surface of nano-titanium dioxide prepared by the thermal reaction of polyol solvent with polyetheramine. The obtained composite formaldehyde remover is used for rapid and durable formaldehyde removal, which comprises the following steps: (1) Precursor preparation Under stirring conditions, alkoxy titanate is added dropwise to low-carbon diol, wherein the volume ratio of the alkoxy titanate to the low-carbon diol is (2.5-5.0):100, and stirring is continued at 30-40°C for 1-2 h. After the mixture is evenly mixed and no white precipitate appears, polyetheramine is added, wherein the molar ratio of the polyetheramine to the alkoxy titanate is 0.2-0.5:1.0, and stirring is continued for 1-2 h to obtain a transparent light yellow solution; (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) is transferred to a polytetrafluoroethylene-lined stainless steel high-pressure reactor with a filling degree of 65-80%, and the reactor is placed in an oven and reacted at 140-180° C. for 14-18 h. After the reaction is completed, the reaction is cooled to room temperature to obtain a reaction product; (3) Treatment of reaction products The reaction product obtained in step (2) was washed three times with water and ethanol respectively, and centrifuged at 10000 rpm to obtain modified nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 60-80 °C for 10-12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

2. The method for preparing the composite formaldehyde remover according to claim 1, characterized in that: The chemical structural formula of the polyetheramine is: In the formula, m is 2 to 8, and n is 2 to 8.

3. The method for preparing the composite formaldehyde remover according to claim 1, characterized in that: The alkoxy titanate is one of n-butyl titanate and tetraisopropyl titanate.

4. The method for preparing the composite formaldehyde remover according to claim 1, characterized in that: The low-carbon diol is one of ethylene glycol, 1,3-propylene glycol and 1,4-butanediol.

5. The method for preparing the composite formaldehyde scavenger according to any one of claims 1 to 4, characterized in that: Prepare as follows: (1) Precursor preparation 3.5 mL of tetraisopropyl titanate was added dropwise to 100.0 mL of 1,3-propylene glycol, and stirred at 30 °C for 2 h. After the mixture was evenly mixed and no white precipitate appeared, 1.97 g of polyetheramine (m=4, n=4) was added, i.e., the molar ratio of polyetheramine (m=4, n=4) to tetraisopropyl titanate was 0.35:1.0, and the mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 69%. The autoclave was placed in an oven and reacted at 140° C. for 18 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reaction product treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 60°C for 12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

6. The method for preparing the composite formaldehyde scavenger according to any one of claims 1 to 4, characterized in that: Prepare as follows: (1) Precursor preparation 3.5 mL of tetraisopropyl titanate was added dropwise to 100.0 mL of 1,3-propylene glycol, and stirred at 30 °C for 2 h. After the mixture was evenly mixed and no white precipitate appeared, 2.20 g of polyetheramine (m=2, n=8) was added, i.e., the molar ratio of polyetheramine (m=2, n=8) to tetraisopropyl titanate was 0.35:1.0, and the mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 69%. The autoclave was placed in an oven and reacted at 140° C. for 18 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reactant treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 60°C for 12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

7. The method for preparing the composite formaldehyde scavenger according to any one of claims 1 to 4, characterized in that: The preparation is carried out according to the following steps: (1) Preparation of precursor 3.5 mL of tetraisopropyl titanate was added dropwise to 100.0 mL of 1,3-propylene glycol, and stirred at 30 °C for 2 h. After the mixture was evenly mixed and no white precipitate appeared, 2.60 g of polyetheramine (m=8, n=2) was added, i.e., the molar ratio of polyetheramine (m=8, n=2) to tetraisopropyl titanate was 0.35:1.0, and the mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 69%. The autoclave was placed in an oven and reacted at 140° C. for 18 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reactant treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 60°C for 12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

8. The method for preparing the composite formaldehyde scavenger according to any one of claims 1 to 4, characterized in that: Prepare as follows: (1) Precursor preparation 2.5 mL of n-butyl titanate was added dropwise to 100.0 mL of 1,3-butanediol, and stirred at 40°C for 1 h. After the mixture was evenly mixed and no white precipitate appeared, 0.70 g of polyetheramine (m=4, n=4) was added, i.e., the molar ratio of polyetheramine (m=4, n=4) to n-butyl titanate was 0.2:1.

0. The mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 68%. The autoclave was placed in an oven and reacted at 180° C. for 14 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reactant treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 80°C for 10 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

9. The method for preparing the composite formaldehyde scavenger according to any one of claims 1 to 4, characterized in that: Prepare as follows: (1) Precursor preparation 5.0 mL of n-butyl titanate was added dropwise to 100.0 mL of ethylene glycol, and stirred at 30°C for 2 h. After the mixture was evenly mixed and no white precipitate appeared, 3.48 g of polyetheramine (m=4, n=4) was added, i.e., the molar ratio of polyetheramine (m=4, n=4) to tetraisopropyl titanate was 0.5:1.0, and the mixture was stirred for 2 h to obtain a transparent light yellow solution. (2) Solvothermal reaction The transparent light yellow solution obtained in step (1) was transferred to a 150.0 mL polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 70%. The autoclave was placed in an oven and reacted at 160° C. for 16 h. After the reaction was completed, the reaction mixture was cooled to room temperature to obtain a reaction product. (3) Reactant treatment The reaction product obtained in step (2) was washed with water and ethanol for three times respectively, and centrifuged at 10000 rpm to obtain nano titanium dioxide wet powder. The wet powder was placed in an oven and baked at 80°C for 10 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain a composite formaldehyde removal agent.

10. A composite formaldehyde removal agent, characterized in that Prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Formaldehyde removal agent

    CN113769549A